Zinc Protoporphyrin Upregulates Heme Oxygenase-1 in PC-3 Cells via the Stress Response Pathway - Simon C. M. Kwok (International Journal of Cell Biology)
Zinc protoporphyrin IX (ZnPP), a naturally occurring molecule formed in iron deficiency or lead poisoning, is a potent competitive inhibitor of heme oxygenase-1 (HO-1). It also regulates expression of HO-1 at the transcriptional level. However, the effect of ZnPP on HO-1 expression is controversial. It was shown to induce HO-1 expression in some cells, but suppress it in others. The objective of this study is to investigate the effect of ZnPP on HO-1 expression in prostate cancer PC-3 cells. Incubation of PC-3 cells with 10 μM ZnPP for 4 h showed only a slight induction of HO-1 mRNA and protein, but the induction was high after 16 h and was maintained through 48 h of incubation. Of all the known responsive elements in the HO-1 promoter, ZnPP activated mainly the stress response elements. Of the various protein kinase inhibitors and antioxidant tested, only Ro 31-8220 abrogated ZnPP-induced HO-1 expression, suggesting that activation of HO-1 gene by ZnPP may involve protein kinase C (PKC). The involvement of PKC α, β, δ, η, θ, and ζ isoforms was ruled out by the use of specific inhibitors. The isoform of PKC involved and participation of other transcription factors remain to be studied.